Faith in Qada' and Qadar and its Implications Against Islamic Religious Education - Wahib, Ahmad (Jurnal Paradigma, 2023)
Something that happens to humans is that God's will is true, but every human being also has his own will. So that in education, students can change learning outcomes by continuing to learn and make a change that will run in harmony and straight with God's will and decision. The study aims to analyze the impact of the beliefs of God's will and provisions on the behaviour of students. This research is qualitative in nature and uses the literature study method. The analysis results show that the will and provisions of Allah make humans more obedient to Allah with more optimism and can understand the wisdom of destiny itself. The implication of qada' and qadar beliefs on Islamic religious education is the inclusion of righteous deeds in students. Based on these results, it can be concluded that belief in qada’ and qadar Allah in students has a very positive impact, one of which is doing good deeds in their daily behaviour which can also be called al-Akhlaq al-Karimah or al-Akhlaq al- Mahmudah.